2004
DOI: 10.1200/jco.2004.07.158
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and Pharmacokinetic Study of the Ribonucleotide Reductase Inhibitor, 3-Aminopyridine-2-Carboxaldehyde Thiosemicarbazone, Administered by 96-Hour Intravenous Continuous Infusion

Abstract: The 96-hour infusion of 3-AP is safe and well tolerated at the recommended phase II doses. Phase II trials of Triapine are ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 29 publications
4
97
0
Order By: Relevance
“…The 3-AP starting dose and schedule were chosen based on prior phase I single agent experience with this drug in solid tumors and hematologic malignancies [7,[10][11][12]. In these trials, a 96-h continuous infusion caused more renal and hepatic toxicity compared with a 2-h infusion given daily for 5 days and repeated every 2 to 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The 3-AP starting dose and schedule were chosen based on prior phase I single agent experience with this drug in solid tumors and hematologic malignancies [7,[10][11][12]. In these trials, a 96-h continuous infusion caused more renal and hepatic toxicity compared with a 2-h infusion given daily for 5 days and repeated every 2 to 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…7 The best studied HCT to date is 3-aminopyridine-2-carboxaldehyde thiosemicarbazone (3-AP), also referred to as Triapine, which has already been examined in several clinical phase I and II trials. 8,9,10 Triapine was found to be safe and effective against hematologic malignancies, e.g. leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…RR contains a tyrosine free radical required for enzymatic reduction of ribonucleotides and 3-AP inactivates RR by neutralizing this free radical. Phase I trials with single-agent 3-AP showed solid tumor activity, including one of two patients with pancreatic cancer who experienced stable disease of three months duration and a 33% decrease in CA 19-9 [11][12][13]. Pharmacokinetics and tolerability data determined that a feasible regimen for phase II testing was 96 mg/m 2 /day as a 2-hour infusion for four days every two weeks.…”
Section: Introductionmentioning
confidence: 99%